Portugal : Fourth Review Under the Extended Arrangement and Request for a Waiver of Applicability of End-June Performance Criteria: Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Portugal. (IMF Staff Country Reports; Country Report, 2012)
This paper discusses findings of the fourth review under an Extended Fund Facility Arrangement with Portugal. One year into the program, the authorities are making progress in reducing economic imbalances. The delicate balance between orderly deleveraging and improving competitiveness also remains in place. A turnaround in investor sentiment has nonetheless proved elusive, reflecting the formidable challenges that remain. Bank deposits remain stable and funding continues to be supported by euro system lending. Market sentiment has improved, although spreads remain high and volatile.